2017
DOI: 10.7759/cureus.1866
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cardiac High-grade Myxofibrosarcoma Presenting with Multiple Brain Metastases: A Case Report

Abstract: Herein we describe the case of a young patient who presented with a recent history of epilepsy due to multiple brain lesions; he did not complain about any cardiopulmonary impairments. The patient died as a consequence of hemorrhagic progression of brain metastatic disease. Regardless of a thorough investigation, the heart tumor remained occult. Primary cardiac tumors are very rare entities. Most of these are benign, but approximately 25% are malignant, and the majority of these are sarcomas. Myxofibrosarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Снижение амплитуды зубца Т может быть вызвано повреждением миокарда и эндокарда. Метастазы МФС сердца могут проявляться эпилептическими приступами, острым нарушением мозгового кровообращения, внутримозговыми гематомами [18].…”
Section: Discussionunclassified
“…Снижение амплитуды зубца Т может быть вызвано повреждением миокарда и эндокарда. Метастазы МФС сердца могут проявляться эпилептическими приступами, острым нарушением мозгового кровообращения, внутримозговыми гематомами [18].…”
Section: Discussionunclassified
“…Intracranial MFS is rare and some reports have described cases without extracranial sites. [ 3 , 6 , 14 , 16 ] Sarrami et al . reported a case of MFS with infiltration of the pons, cerebellum, and basal surface of the left temporal lobe without any visible masses.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial MFS is rare and some reports have described cases without extracranial sites. [3,6,14,16] Sarrami et al reported a case of MFS with infiltration of the pons, cerebellum, and basal surface of the left temporal lobe without any visible masses. [16] A 55-year-old man presented with MFS presenting as an acute cerebral hemorrhage, with subsequent development of lung metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myxo brosarcoma is categorized from low-grade neoplasm to high-grade neoplasm. A low-grade myxo brosarcoma tends to metastasize locally while high-grade myxo brosarcomas invade local and adjacent tissues and are associated with distant metastasis to the lung, bone, brain, and lymph nodes (9). The local recurrence rate and distant metastasis rate were 42.9% and 19.0% respectively (4).…”
Section: Discussionmentioning
confidence: 99%